Batman year one artist's edition - Mazzucchelli, David 1960- (IDW Publishing, 2024)
Originally published in single magazine form in Batman #404-407, ©1987 DC Comics
Keywords: Batman -- Fiktive Gestalt; Comic books, strips, etc / United States; Graphic novels / United States; Batman (Fictitious character) / Comic books, strips, etc; Heroes / Comic books, strips, etc; Graphic novels; Batman / (Fictitious character) / https://id.oclc.org/worldcat/entity/E39PBJhH4HF6T4HFMvqPgbBVmd; Good and evil; Batman (Fictional character) / Fiction; Heroes and heroines / Fiction; Good and evil / Fiction; Comic books, strips, etc; Comics (Graphic works); Bandes dessinées; Comic